2013
DOI: 10.1093/jxb/ert162
|View full text |Cite
|
Sign up to set email alerts
|

SlERF36, an EAR-motif-containing ERF gene from tomato, alters stomatal density and modulates photosynthesis and growth

Abstract: The AP2 domain class of transcription factors is a large family of genes with various roles in plant development and adaptation but with very little functional information in plants other than Arabidopsis. Here, the characterization of an EAR motif-containing transcription factor, SlERF36, from tomato that affects stomatal density, conductance, and photosynthesis is described. Heterologous expression of SlERF36 under the CaMV35S promoter in tobacco leads to a 25–35% reduction in stomatal density but without an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 45 publications
2
33
1
Order By: Relevance
“…This contention is in tune with our demonstration that RIN regulates SlHSP gene transcription and the fact that RIN expression occurs at the onset of ripening of tomato fruit 35 . A model on the transcriptional regulation that interfaces ethylene, RIN and class I SlHSPs , including possible components involved, is presented in Fig.…”
Section: Discussionsupporting
confidence: 74%
“…This contention is in tune with our demonstration that RIN regulates SlHSP gene transcription and the fact that RIN expression occurs at the onset of ripening of tomato fruit 35 . A model on the transcriptional regulation that interfaces ethylene, RIN and class I SlHSPs , including possible components involved, is presented in Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Our previous results had shown that over-expression of SlERF36 affects stomatal density and that many of the defects in photosynthetic parameters were most likely associated with adaptive responses due to reduced stomatal number [22]. To test whether the reduction in photosynthetic parameters was associated with stomatal number, we measured the stomatal density on the abaxial leaf surface (7 th leaf from bottom of 30-day-old plants) of control and transgenic lines.…”
Section: Resultsmentioning
confidence: 99%
“…The availability of the entire genome sequence of several plant species has made it possible to confirm the relatively well-conserved organisation of the AP2/ERF superfamily with 147, 149, 202, 180, and 146 genes in Arabidopsis thaliana, Vitis vinifera, Populus trichocarpa, Oryza sativa, and Solanum lycopersicon, respectively, mostly represented by the ERF family (Nakano et al 2006;Zhuang et al 2008;Licausi et al 2010;Zhuang et al 2011;Pirrello et al 2012). The ERF subfamily has also been characterised in tobacco (Park et al 2001;Fischer and Droge-Laser 2004;), Arabidopsis (Broun et al 2004;Yang et al 2005;Mehrnia et al 2013), peppers (Yi et al 2004;Youm et al 2008), tomatoes (Zhang et al 2009;Upadhyay et al 2013), corn (Chuck et al 2002;Qin et al 2004), and rice (Cao et al 2006;Xu et al 2011). Overexpression of some ERF genes enhanced the plants' resistance to biotic and abiotic stresses (Berrocal-Lobo et al 2002;Fischer and Dröge-Laser 2004;Xu et al 2011).…”
Section: Discussionmentioning
confidence: 98%